A teleseismic shear-wave splitting study to investigate mantle flow around South America and implications for plate-driving forces - Helffrich, George; Wiens, Douglas A.; Vera, Emilio; Barrientos, Sergio; Shore, Patrick; Robertson, Stacey; Adaros, Rodrigo (Geophysical Journal International, 2002)
Closure of the Pacific Ocean basin by the convergence of its surrounding plates, some of which have deep continental roots, implies that there is net mass flux out of the mantle under the Pacific. Here we report on a shear-wave splitting study designed to test the prediction that there should be flow around its southern margin. Our results show no evidence for present-day flow around the tip of southern South America. Instead, the results suggest present-day flow directions in the southern Atlantic that parallel the South American absolute plate motion direction, even under Antarctica. The results also provide evidence for absolute plate motion driven by the basal drag of ocean basin-scale mantle flow, and suggest that ∼200 km thick flow boundary layers exist under South America and Antarctica, and also demonstrate that mantle flow directions cannot be reliably inferred from present-day plate morphology.